2022
DOI: 10.3389/fmolb.2022.800008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights Into the Effects of Interactions With Iron and Copper Ions on Ferritin From the Blood Clam Tegillarca granosa

Abstract: In addition to its role as an iron storage protein, ferritin can function as a major detoxification component in the innate immune defense, and Cu2+ ions can also play crucial antibacterial roles in the blood clam, Tegillarca granosa. However, the mechanism of interaction between iron and copper in recombinant Tegillarca granosa ferritin (TgFer) remains to be investigated. In this study, we investigated the crystal structure of TgFer and examined the effects of Fe2+ and Cu2+ ions on the TgFer structure and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…On the basis of these results, it can be roughly concluded that the residues Asp129 and Glu132 at the three-fold channel in AjFER are probably involved in Fe 2+ capture and its translocation to the internal cavity of the protein, from where Fe 2+ reaches the ferroxidase center, similar to that proposed for BfMF [43]. Furthermore, our results confirm the ferroxidase center of AjFER indeed has a function in iron oxidation and the Glu168 residue in AjFER can act as a potential metal-ion binding site at the four-fold channel, similar to observations in previous studies [9,14]. In addition, the variants (MF, M3, and M4 proteins) exhibited lower unfolding temperatures than native AjFER, suggesting that mutations of the potential metal-binding sites in AjFER could have varying effects on its thermal stability and structural integrity.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…On the basis of these results, it can be roughly concluded that the residues Asp129 and Glu132 at the three-fold channel in AjFER are probably involved in Fe 2+ capture and its translocation to the internal cavity of the protein, from where Fe 2+ reaches the ferroxidase center, similar to that proposed for BfMF [43]. Furthermore, our results confirm the ferroxidase center of AjFER indeed has a function in iron oxidation and the Glu168 residue in AjFER can act as a potential metal-ion binding site at the four-fold channel, similar to observations in previous studies [9,14]. In addition, the variants (MF, M3, and M4 proteins) exhibited lower unfolding temperatures than native AjFER, suggesting that mutations of the potential metal-binding sites in AjFER could have varying effects on its thermal stability and structural integrity.…”
Section: Discussionsupporting
confidence: 90%
“…A metal ion binding to the Cys128 residue (forming the Cd-S-Cys charge transfer complex) at the three-fold channel of ferritin revealed that metal ion coordination to sulfur can complement ionic binding during Fe 2+ transit through ion channels [43,44]. Additionally, consistent with most ferritins from marine invertebrates [7,9,14,15,45], two metal ion-binding sites (i.e., sites A and B) in the ferroxidase center were observed in the middle of four α-helical bundles per subunit in the M3 protein (Figure 4E). On the basis of the positive electron density map and the coordination environment of iron around the ferroxi-dase site, two iron ions were assigned in sites A and B of the ferroxidase center of the M3 protein.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations